2018
DOI: 10.1016/j.jpainsymman.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the IPOS-Renal Symptom Survey in Advanced Kidney Disease: A Cross-sectional Study

Abstract: The IPOS-renal surveys, patient and staff versions, have good test-retest reliability, internal consistency, and construct validity in patients with advanced kidney disease and their nurses. We recommend their use in symptom assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 30 publications
(18 reference statements)
1
55
0
1
Order By: Relevance
“…[35] However, very few studies validated these two measures in our target population (stages 4 and 5 CKD). [35,36] The review also identified the IPOS-Renal (11 items), [37] which was undergoing validation at the time.…”
Section: Development Of the Renal Eprommentioning
confidence: 99%
“…[35] However, very few studies validated these two measures in our target population (stages 4 and 5 CKD). [35,36] The review also identified the IPOS-Renal (11 items), [37] which was undergoing validation at the time.…”
Section: Development Of the Renal Eprommentioning
confidence: 99%
“…POS is widely used in clinical care, audit, research, and training and it was validated in several languages [4,5]. The POS measures have been used in different patients populations such as patients with cancer, respiratory, heart, renal or liver failure, and neurological diseases [6][7][8][9][10]. POS-S was developed as an addition to POS to be used as a brief tool specifically focused on physical symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…POS is widely used in clinical care, audit, research, and training and it was validated in several languages (4,5). The POS measures have been used in different patients populations such as patients with cancer, respiratory, heart, renal or liver failure, and neurological diseases (6)(7)(8)(9)(10). POS-S was developed as an addition to POS to be used as a brief tool specifically focused on physical symptoms (11).…”
Section: Introductionmentioning
confidence: 99%